Transfer of arrhythmia substrate targets from the cardiac electroanatomical and imaging modalities to the planning computed tomography scan for stereotactic arrhythmia radioablation for refractory ventricular tachycardia: a state-of-the-art review on software developments on behalf of the STOPSTORM.eu consortium - Bekke, Rachel M. A. ter; Hohmann, Stephan; Xie, Jingyang; Grehn, Melanie; Verhoeven, Karolien; Volders, Paul G. A.; Mihl, Casper; Kaya, Yeşim Selma; Manninger, Martin; Scherr, Daniel; Corradini, Stefanie; Schweikard, Achim; et al. (Radiotherapy and oncology, 2025)
Stereotactic arrhythmia radioablation (STAR) for ventricular tachycardia (VT) is a non-invasive treatment modality to reduce the VT burden by delivering a single high radiation dose to the arrhythmogenic substrate. Identification and delineation of the arrhythmogenic substrate, definition of the radiation target, and transfer of this target across different imaging modalities from the invasive electroanatomic map (EAM) to the planning computed tomography (CT) scan are key to the success of therapeutic radiation. The VT substrate is identified using EAM data and co-localized with radiological correlates of the ventricular scar. Precise transfer to the non-ECG-gated treatment planning CT is essential for safe and effective STAR delivery. Current challenges include translating the endocardial or epicardial EAM surface target into a 3D cardiac target volume (CTV), reconciling different acquisition methods (e.g., (exhale-gated) EAM, contrast-enhanced ECG-gated CT angiography, and non-gated non-contrast planning CT), and achieving accurate CTV transfer using multi-modal image integration. Early approaches relied on manual delineation using side-by-side EAM and CT rendering, leading to poor reproducibility and potential treatment failure. Emerging (semi)auto-segmentation software based on the American Heart Association (AHA) 17-segment left ventricular model offers promise but lacks standardized weighing of identified segments and methods for handling partially involved segments. More recently, 2D-to-3D and 3D-to-3D target transfer methods, including commercial and in-house computer-aided tools, have been developed to address these difficulties. Currently, a standardized workflow has not been established. This review addresses the need to standardize CTV definitions and transfer workflows, assessing available tools and proposing quality assurance measures based on recommendations of the STOPSTORM.eu consortium.
Online verfügbar: 27. Juni 2025, Artikelversion: 2. Juli 2025
Gesehen am 18.08.2025